2017
DOI: 10.1155/2017/5121032
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine Deficiency Leading to Refractory Lactic Acidosis in a Pediatric Patient

Abstract: Thiamine plays a critical role in energy metabolism. Critically ill children and adults may develop thiamine deficiency with ultimately increased mortality due to potentially irreversible consequences of severe type B lactic acidosis. We report a case of an unvaccinated term neonate with malignant pertussis requiring extracorporeal membrane oxygenation and continuous renal replacement therapy, who developed profound lactic acidosis of unknown etiology. After countless evaluations for likely causes, the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 13 publications
1
25
1
Order By: Relevance
“…Studies included in the scoping review investigated serum/plasma levels, reporting micronutrient status was determined on admission day in majority of patients. There were a number of studies describing low serum/plasma micronutrient levels during critical illness including thiamine, riboflavin, folate, vitamin B6, vitamin B12, vitamin A, β-carotene, zinc, selenium, iron and chromium [ [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ], as well as studies describing serum/plasma levels unchanged or high during critical illness vitamin E, vitamin B6, copper and manganese [ 38 , [42] , [43] , [44] ]. A number of these studies reported factors associated with serum/plasma levels of micronutrients levels including the use of continuous renal replacement therapy, cardiac surgery and systemic inflammatory response [ 21 , 22 , 30 , 31 , 37 , 38 , 42 , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies included in the scoping review investigated serum/plasma levels, reporting micronutrient status was determined on admission day in majority of patients. There were a number of studies describing low serum/plasma micronutrient levels during critical illness including thiamine, riboflavin, folate, vitamin B6, vitamin B12, vitamin A, β-carotene, zinc, selenium, iron and chromium [ [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ], as well as studies describing serum/plasma levels unchanged or high during critical illness vitamin E, vitamin B6, copper and manganese [ 38 , [42] , [43] , [44] ]. A number of these studies reported factors associated with serum/plasma levels of micronutrients levels including the use of continuous renal replacement therapy, cardiac surgery and systemic inflammatory response [ 21 , 22 , 30 , 31 , 37 , 38 , 42 , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] ].…”
Section: Resultsmentioning
confidence: 99%
“… Micronutrient Role Age Reference range (US) Reference range (SI) Levels reported Median (interquartile range) Direction of serum change Low No change ≈ High Studies describing changes in serum levels of micronutrients during critical illness Thiamine/Vitamin B1 (p) Thiamine is involved in a number of intermediate metabolism associated with energy production including converting pyruvate from glucose into acetyl co-enzyme A for entry into the Krebs cycle, during thiamine deficiency alters intermediate metabolism resulting in lactic acidosis [ 31 ]. 5.3–7.9 μg/mL 5.5 μg/mL (5.1, 6.5) Low Low serum thiamine levels [ [32] , [33] , [34] , 36 , 65 ] have been reported in 12.5–32% patients [ 31 , 42 , 47 ] Pyridoxine/Vitamin B6 (p) Vitamin B6 is required for 150 enzyme reactions, including inflammatory pathways including the kynurenine pathway, sphingosine 1-phosphate metabolism, the transsulfuration pathway, and serine and glycine metabolism [ 95 ]. 5–50 μg/l Levels not reported Low No change ≈ A single case report of vitamin B6 (and thiamine deficiency) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations